MOTIVATION AS THE KEY TO SUCCESS IN THE PROCESS OF SECOND LANGUAGE ACQUISITION - Eliza, Tiara (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2021)
Gaining knowledge and experience when learning a new language will get our own satisfaction. Being based on motivation and the desire to be better is a very good start in the process of learning a new language. Starting with an understanding of motivation to the theory that makes motivation the key to success in learning L2. This lesson is expected to be a provision for success and understanding of L2 to be applied based on the objectives of each person who learns it.